76.1k views
3 votes
Multiply each term inside the parentheses by the factor outside the parentheses 2(x - 4) = 2 x + 2(-4) Multiply Simplify.2(×-4)=2x+2(-4)

User Liam W
by
4.9k points

1 Answer

4 votes

We have the expression:


2(x-4)=2x+2(-4)

We solve as follows:


2x-8=2x-8

If we want to simplify further, we will get:


2x=2x\Rightarrow x=x\Rightarrow0=0

***

In order to simplify the expression:


2(x-4)=2x+2(-4)

We multiply 2 times x and add 2 times -4, that is:


2x+2(-4)=2x+2(-4)

Now, we multiply 2 times -4 in both sides, that is:


2x-8=2x-8

User Diya
by
5.6k points